2016
DOI: 10.4000/cybergeo.27517
|View full text |Cite
|
Sign up to set email alerts
|

La dynamique spatiale des activités logistiques dans les aires urbaines françaises

Abstract: The number and intensity of freight flows have increased over the last decades, in a context of fast integration of the world economy and deep transformation of production and distribution systems. In France, to cope with this new complexity, many logistics activities have been created across the country and have since concentrated in largest urban areas. Within them, new locations become increasingly suburban, in order to take advantage of the availability of large parcels and where land prices are cheaper. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the movement of logistics activities to fringes is not straightforward: its intensity can vary considerably between urban areas and even within a single metropolitan area over different periods. Guerrero and Proulhac (2016) showed that the most frequent decentralization pattern in French urban areas is initial sprawl, followed by the emergence of a few suburban centres. In some cases, a period of decentralization is followed by recentralization (Guerrero and Proulhac, 2016;Heitz and Dablanc, 2015), sometimes due to the adoption of more conservative strategies on the part of warehouse investors and developers (Raimbault, 2016).…”
Section: Changes In the Location Of Logistics Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the movement of logistics activities to fringes is not straightforward: its intensity can vary considerably between urban areas and even within a single metropolitan area over different periods. Guerrero and Proulhac (2016) showed that the most frequent decentralization pattern in French urban areas is initial sprawl, followed by the emergence of a few suburban centres. In some cases, a period of decentralization is followed by recentralization (Guerrero and Proulhac, 2016;Heitz and Dablanc, 2015), sometimes due to the adoption of more conservative strategies on the part of warehouse investors and developers (Raimbault, 2016).…”
Section: Changes In the Location Of Logistics Activitiesmentioning
confidence: 99%
“…Guerrero and Proulhac (2016) showed that the most frequent decentralization pattern in French urban areas is initial sprawl, followed by the emergence of a few suburban centres. In some cases, a period of decentralization is followed by recentralization (Guerrero and Proulhac, 2016;Heitz and Dablanc, 2015), sometimes due to the adoption of more conservative strategies on the part of warehouse investors and developers (Raimbault, 2016). Heitz and Dablanc (2015) conducted a centrography study of the logistics firms in the extended Paris region between 2000 and 2012.…”
Section: Changes In the Location Of Logistics Activitiesmentioning
confidence: 99%
“…The continent of Europe is a good example to show the time mismatch. Traditionally, capitalist European states have been struggling with the process of residential suburbanisation for a long time (Gerten et al 2019, Guerrero, Proulhac 2016. For this reason, in some countries, there is even another phase of the urbanisation process, which is called "reurbanisation", or the re-settlement of core cities by people from the suburbs or rural areas ____________________ DOI: https://doi.org/10.33542/GC2022-1-02 (Carlucci et al 2018).…”
Section: Introductionmentioning
confidence: 99%